Kecenderungan Kenakalan Remaja Ditinjau Dari Kekuatan Karakter Dan Persepsi Komunikasi Empatik Orangtua - Amelia Dwi Syifaunnufush; Rachmy Diana (UIN Sunan Kalijaga, 2017)
The aim of this research was to understand the relationship between character strength and perception of parental emphatic communication with tendency of juvenile delinquency. The population in this study was student of SMK Piri 1 Yogyakarta with a sample of 59 student in 15-18 years old. Sampling techniques were used is purposive sampling. Data collection instrument were used in this study is Likert Scale, consist of Tendency of Juvenile Delinquency Scale, Character Strength Scale, and Perception of Parental Emphatic Communication Scale. Statistical analysis techniques used are regression. Result of analyzed data obtained correlation coefficient (R) = 0,467 with p = 0.000 (p<0.05). As it showed that there was significant correlation between character strength and perception of parental empathic communication with tendency of juvenile delinquency. Contribution character strength and perception of parental emphatic communication 21,8% (R square = 0,218). Partially, analysis variable character strength obtained correlation coefficient (R) = 0,467 with p = 0,000 (p<0,05) and R square = -0,218. As it showed that there was significant correlation between character strength with tendency of juvenile delinquency. Whereas the results of analysis variable perception of parental emphatic communication obtained correlation coefficient (R) = -0,241 with p = 0,066 (p<0,05) and R square = 0,058. As it showed that there wasn’t significant correlation between perception of parental emphatic communication with tendency of juvenile delinquency.